2020
DOI: 10.1177/2397002220952738
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance policies in high performance organisations: A comparative interview study with millennials in Dutch consultancies

Abstract: The literature on work-life balance primarily focuses on how individuals cope with high work demands. This study, however, investigates how young professionals experience the work-life balance support offered by organisations. Twenty-four millennial consultants were interviewed to explore their perceptions of work-life balance and organisational support policies in an extreme work context. Twelve consultants worked for strategy houses with an average working week of around 60 hours, while the other 12 worked f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 83 publications
(149 reference statements)
1
21
0
Order By: Relevance
“…Consequently, some of the respondents were able to finish their work schedule on time and this enabled them to perform other non-work activities at home and in the university. These findings are in line with the earlier results obtained by Bouwmeester et al (2020), which reported employees who practice job sharing with colleagues in demanding times experience higher work-life satisfaction. Again, the findings are consistent with the basic tenets of the ecological systems theory that postulates that to attain a healthy well-being, individuals must rely on resources in their environment.…”
Section: Co-worker Supportsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, some of the respondents were able to finish their work schedule on time and this enabled them to perform other non-work activities at home and in the university. These findings are in line with the earlier results obtained by Bouwmeester et al (2020), which reported employees who practice job sharing with colleagues in demanding times experience higher work-life satisfaction. Again, the findings are consistent with the basic tenets of the ecological systems theory that postulates that to attain a healthy well-being, individuals must rely on resources in their environment.…”
Section: Co-worker Supportsupporting
confidence: 93%
“…Such interventions when properly managed can also nurture positive psychological health amongst employees because, in addition to continuing their work from their preferred location, they get to have a life outside work. The practice of job sharing and job outsourcing has also been identified as an effective strategy to contain work pressures and job overload (Bouwmeester, Atkinson, Noury, & Ruotsalainen, 2020). Working parents have also been observed to employ active adjustment techniques such as house help, leaving the office on time, planning work schedule in consultation with the spouse, working from home/part-time (Murthy & Shastri, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…What do we know about this issue based on previous studies? The consultant literature states that consultants are asked to work on average over 60 h a week in certain settings (Alvesson & Robertson, 2006;Bouwmeester et al, 2021). Promotions only occur through high commitment, and workers can feel anxious about their current status and performance (Gill, 2015, p. 309).…”
Section: The Issue-experiencing Overly Pressuring Leadershipmentioning
confidence: 99%
“…When it comes to the consultantmanager relationship, there are no such consequences, and many graduates even love to start working at consultancies (Rivera, 2016). Consultancies seem somehow immune to these critical judgements, or very good at neutralizing or normalizing them (Ashforth et al, 2007;Bouwmeester et al, 2021). While consulting research has identified various stressors, disturbed work-life balance and reduced employee wellbeing (Meriläinen et al, 2004;Mühlhaus & Bouwmeester, 2016;Noury et al, 2017;O'Mahoney, 2007), pressuring management is no big issue yet, and not addressed in codes of conduct either.…”
Section: The Issue-experiencing Overly Pressuring Leadershipmentioning
confidence: 99%
“…Alvesson and Einola, 2018;Blagoev et al, 2018;Costas and Kärreman, 2016;Stein, 2017). Indeed, consultants themselves highlight the physical and psychological stresses of their work (see Gill, 2015;Mühlhaus and Bouwmeester, 2016), the sacrifices of their work-life balance (Bouwmeester et al, 2021;Noury et al, 2017), and the consequences for their physical and mental health (O'Mahoney, 2007).…”
Section: Introductionmentioning
confidence: 99%